Use of person-centered goals to direct interdisciplinary care for military service members and Veterans with chronic mTBI and co-occurring psychological conditions - Wallace, Tracey D.; McCauley, Katherine L.; Hodge, April T.; Moran, Tim P.; Porter, Stephen T.; Whaley, Maya C.; Gore, Russell K. (Frontiers in Neurology, 2022)
Objective: To explore the use of person-centered goals (PCGs) to direct interdisciplinary care to support PCG attainment in military service members and Veterans (SM/Vs) with chronic mild traumatic brain injury (mTBI) and co-occurring psychological conditions. Methods: A retrospective chart review was completed for 146 United States military SM/Vs reporting chronic symptoms following mTBI and co-occurring psychological conditions who received care in the SHARE Military Initiative intensive outpatient program, a donor-funded program administered by a not-for-profit hospital, between April 1, 2015 and March 31, 2019. PCGs were used to direct care consisting of individual and group-based interventions and therapies delivered by an interdisciplinary, co-located team including behavioral health, case management, neurology or physiatry, nursing, occupational therapy, physical therapy, recreation therapy, speech-language pathology, and transition support. The primary outcome measure was PCG attainment measured via goal attainment scaling. Results: Increased PCG attainment was demonstrated at program discharge and throughout the first year following program discharge. Predictors of goal attainment at discharge included longer participation in treatment, greater reduction in depressive symptoms and greater improvement in adjustment at discharge, male gender, and higher cognitive and physical abilities on admission. Conclusions: This sample of military SM/Vs with mTBI and co-occurring psychological conditions who received intensive, interdisciplinary, PCG directed care demonstrated increased PCG attainment at program discharge which further increased with transition support over the year post-discharge. Results suggest PGC goal directed care is a feasible, promising methodology of individualizing treatment in this population. This exploratory study lays a foundation for future prospective, controlled, comparative effectiveness research that will further understanding of the effectiveness of intensive, interdisciplinary, PCG directed care.